Design of a high performance electrode composed of porous nickel–cobalt layered double hydroxide nanosheets supported on vertical graphene fibers for flexible supercapacitors. (9th April 2020) - Song, Yanping; Zhang, Jixiang; Li, Nian; Han, Shuai; Xu, Shihao; Yin, Jun; Qu, WanLi; Liu, Cui; Zhang, Shudong; Wang, Zhenyang
Abstract : A flexible supercapacitor based on a NC-LDH/LIG composite with high electrochemical performance was prepared via a laser-induced technology. Abstract : The micro/nanostructure of electrode materials is one of the key factors affecting the performance of supercapacitors. Here, a hybrid electrode composed of nickel–cobalt layered double hydroxide (NC-LDH) nanosheets supported on vertical graphene fibers was designed for flexible supercapacitors. An efficient and low-cost laser-induced technology was explored to synthesize vertical graphene fibers using polyphenylene sulfide (PPS) as a precursor. By double laser writing in two directions perpendicular to each other, laser-induced graphene (LIG) fibers with improved conductivity and optimized morphology were achieved. As a result, porous NC-LDH nanosheets with high specific capacitance can be uniformly loaded onto LIG fibers by the electrodeposition method. The as-obtained composite with fast electron transfer and efficient ion transport properties was used as a supercapacitor electrode, achieving an ultrahigh specific capacitance of 4503 mF cm −2 at 1.0 mA cm −2 in a standard three-electrode system. Furthermore, a flexible asymmetric supercapacitor (ASC) was successfully assembled using NC-LDH/LIG as the positive electrode and activated carbon as the negative electrode with the PVA–KOH gel electrolyte, obtaining a high energy density of 219 μW h cm −2 at a power density of 378 μW cm −2 . These excellent electrochemical properties are attributed to the rational structural design of the electrode and the synergistic effect of each electrode component, which exhibits great application prospects in flexible energy storage devices.